Addressing social determinants of health in individuals with mental disorders in clinical practice: review and recommendations - Dilip V. Jeste; Jeffery Smith; Roberto Lewis-Fernández; Elyn R. Saks; Peter J. Na; Robert H. Pietrzak; McKenzie Quinn; Ronald C. Kessler (Translational Psychiatry)
Abstract Social determinants of health have been shown to have a greater impact on overall health than traditionally considered medical risk factors, especially in people with mental disorders. It is the primary responsibility of healthcare providers to ensure that persons with psychiatric disorders are actively helped in reducing the adverse effects of SDoMH on their health and healthcare. Yet, the current clinical psychiatric practice in the U.S. does not have any standardized guidelines for evaluating or addressing these critical factors even among individuals who are receiving psychiatric and other medical treatment. Although there are several barriers to implementing such interventions, there are also practical approaches to address selected social determinants of mental health and improve the well-being of our patients. In this article, we review the literature on the assessment of relevant social factors and pragmatic psychosocial strategies at the individual, family, and community levels to help reduce their adverse impact. We offer guidelines for psychiatric clinicians and case managers to improve the health and quality of life of persons with mental disorders, using sustained inter-professional collaborative efforts.